(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
In the development of patent law, inventive step has traditionally been viewed as something essentially human. This paradigm is now being challenged by the possibility of using creative AI systems capable of independently generating new inventions: The so-called creative — physical or virtual — programs and robots have therefore triggered a series of considerations that are not easily resolved within the current framework of patent law. Indeed, there is no consensus that machines can be called inventors. In this paper, we will attempt to explore the complex relationship between creation, protection, human inventiveness, and intelligent, creative and interactive robots and AI systems. In particular, we will clarify whether inventions brought about by AI require a complete reassessment of key concepts in patent matters.